Under the sign of Hryhoriy Skovoroda - Boychuk, Yu.; Berezhna, S. (New Collegium, 2023)
The 300th anniversary of Hryhoriy Skovoroda was included in the list of UNESCO jubilee dates in 2022. The outstanding Ukrainian left his descendants a phenomenal spiritual and pedagogical heritage, which does not lose its unique cognitive, ethical, educational, aesthetic significance even now, in the most difficult times in the history of our country. On the eve of the important date (from November 30 to December 2, 2022) at the Kharkiv National Pedagogical University named after H.S. Skovorody held solemn events dedicated to the anniversary of the Ukrainian philosopher.